2018
DOI: 10.1080/07315724.2018.1476194
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Magnesium Status, Dietary Magnesium Intake, and Metabolic Control in Patients with Type 2 Diabetes Mellitus

Abstract: Hypomagnesemia in T2DM is directly associated with poor metabolic control. Clinical assessment should, therefore, focus on augmentation of magnesium status and adequate magnesium intake in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…However, the diets of the people in this area are roughly similar to those of most people in Ghana. Fourth, magnesium intake from drinking water was not assessed, which is consistent with previous studies [5][6][7][8][9]. The primary source of drinking water in our study was tap water.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the diets of the people in this area are roughly similar to those of most people in Ghana. Fourth, magnesium intake from drinking water was not assessed, which is consistent with previous studies [5][6][7][8][9]. The primary source of drinking water in our study was tap water.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have reported that low magnesium intake is associated with type 2 diabetes mellitus (T2DM) [3][4][5][6], and randomized controlled trials show that magnesium supplementation improves glucose parameters in adults with diabetes and improves insulin sensitivity in those at high risk of diabetes [7][8][9][10]. However, the majority of research has been conducted in high-income countries [3][4][5][6][7][8][9][10], and no study has examined the relationship between magnesium intake and T2DM in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, it has been suggested that hypomagnesemia may induce altered cellular glucose transport, defective tyrosine-kinase activity, and insulin receptor autophosphorylation, post-receptor impairment in insulin action by influencing intracellular signaling cascade and processing, reduced pancreatic insulin secretion, and worsening of insulin resistance in diabetics [37,38,39,40]. Above all, defective insulin receptor phosphorylation is regarded as the main mechanism by which hypomagnesemia contributes to insulin resistance in T2DM patients [24], and some epidemiological studies have suggested that adequate Mg 2+ intake may reduce T2DM incidence [41].…”
Section: Discussionmentioning
confidence: 99%
“…These authors found low transferrin saturation in patients with diabesity, which correlated with IR, inflammation, and abdominal adiposity, mainly in women. On the other hand, it has also been observed that a deficient intake of zinc, potassium, calcium, and magnesium could alter glycemic control in individuals with DM2, increasing Hba1C values [138,139].…”
Section: Mineral and Trace Elementsmentioning
confidence: 99%